Entering and Leaving Self-Employment: A Panel Data Analysis for 12 Developing Countries - Yoon Y. Cho; David A. Robalino; Jose M. Romero (Institute for the Study of Labor (IZA), 2015)
This paper examines the determinants of labor market transitions into and out of self-employment (own-account work and employer), using panel data from 12 developing countries in multiple regions. Despite cross-country heterogeneity, a few consistent patterns emerge. Entering the labor market through, or moving from wage employment into, own-account work is generally infrequent even during economic downturns, suggesting that own-account work is not an automatic choice for subsistence. Some better educated and older workers become employers by starting their business with paid employees or by growing their business from own-account work, although the overall chances of becoming employers are quite low and employer downsizing to own-account work is common. Reflecting the frequent transitions between own-account work and employer statuses, in many cases, particularly in middle-income countries, a substantial proportion of own-account workers share common characteristics with employers (and vice versa). The results suggest that there is a role for programs to support employers sustain its activities and facilitate own-account workers to become employers.
Keywords: O12; J24; 330; labor market transitions; self-employment; entrepreneurship